Case To Action Kaitannya Dengan Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Kassi-kassi - Yulianti, Yulianti; Abdullah, Tahir; Yusriani, Yusriani (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Many theories are references to changes in health behavior, but here researchers are interested in using Case To Action Theory. This theory explains how external events can motivate someone to act. The study aims to determine the relationship of a case to action theory to the exclusive breastfeeding in the work area Community Health Area Kassi-Kassi. This type of research was observational analytic with a cross-sectional study approach.Sampling technique is purposive sampling, 140 babies from all 238 infants aged 6-11 months. Retrieval of data using a questionnaire and analyzed by chi-square test using Yates correction formula which is processed using the Statistical Product and Service Solution (SPSS) Program. The results of this study indicate that husband/family support has a significant relationship to exclusive breastfeeding with a Pvalue=0,001 < Î±= 0,05. Support of health workers has a significant relationship to exclusive breastfeeding with a Pvalue=0,000 < Î±= 0,05. Whereas media exposure has a significant relationship to exclusive breastfeeding with a Pvalue=0,000 < Î±= 0,05 From this study it was concluded that overall there was a significant relationship between case to action towards exclusive breastfeeding.